Using the nonlinear layer model for estimation of characteristics of high-power ultrashort laser pulse beams propagating along an aerospace path - Zemlyanov, Alexander A. (Proceedings of SPIE)
The propagation of high-power ultrashort laser pulses on aerospace paths when laser radiation is sent from the Earth into space is analyzed theoretically. Titanium-sapphire and CO2 lasers with femtosecond and picosecond pulse durations, respectively, are considered as radiation sources. The effective intensity and effective radius of curvature of the wavefront of high-power laser beams are estimated on the basis of the nonlinear layer model. It is shown that, on the whole, the use of a CO2 laser makes it possible to achieve more precise focusing of radiation on an object during energy transfer under the conditions of power losses caused by strong molecular absorption. Also, more precise focusing on aerospace paths up to 400 km long is ensured by the use of a laser beam with a lower peak power and a larger initial radius.